Ocular signs and symptoms and vitamin A status in patients with cystic fibrosis treated with daily vitamin A supplements. Issue 6 (1st June 1999) - Ansari, Ejaz A; Sahni, Kamal; Etherington, Christine; Morton, Alison; Conway, Steven P; Moya, Eduardo; Littlewood, James M
Abstract : BACKGROUND/AIMS: Patients with cystic fibrosis (CF) may have low plasma vitamin A levels from malabsorption, zinc deficiency, liver disease, or poor compliance with prescribed supplements. In view of the increasing number of adults with CF, many of whom drive cars, it is important to assess vitamin A status. In our centre an attempt has been made to achieve normal levels of fat soluble vitamins by annual estimation of plasma levels and appropriate oral supplementation. This study aimed to determine if this approach prevents vitamin A deficiency and the consequent problems with dark adaptation. METHODS: The study was conducted at the regional adult and paediatric cystic fibrosis unit and the patients were recruited from there. Dark adaptation studies were conducted at the department of ophthalmology, St James's University Hospital. All patients are regularly seen in the outpatient department by a CF specialist dietitian and have a comprehensive annual dietary assessment. 28 patients had the following investigations: serum retinol, plasma zinc, serum retinol binding protein, liver function tests, dark adaptation, contrast sensitivity, and anterior ocular surface status. 25 age and sex matched controls without CF or ocular pathology were also recruited for the dark adaptation study. RESULTS: None of the patients had vitamin A deficiency, the median value of serum retinol being 48 μg/dl, range 31–80 μg/dl (normal range 30–80 μg/dl). Dark adaptation was normal in all cases compared with the control group where the mean value was 3.4 log units of threshold luminance (95% confidence interval 2.4–4.0). None of the test group had a value of threshold luminance 2 SD above the mean value for the control group. Eight patients had reduced contrast sensitivity. The median value for serum zinc was 14.2 μmol/ l, range 13–81 μmol/l (normal range 8–23 μmol/l) and the median value for retinol binding protein was 36 mg/l, range 13–81 mg/l (normal range 35–58 mg/l). There was no correlation between dark adaptation and serum retinol, zinc, or retinol binding protein. Two patients had clinical evidence of dry eye. CONCLUSION: Regular estimates of plasma vitamin A together with appropriate supplementation and expert dietetic review can maintain normal dark adaptation in patients with cystic fibrosis. The occurrence of reduced contrast sensitivity function is well documented but remains an unexplained phenomenon and deserves further study.